Geochemical characteristics and petrogenetic process of late cretaceous granites in the southern Tibet Gangdese Tectonic Belt - Zheng, Feifei; Zhai, Xinwei; Guo, Zhiang; Wang, Erteng; Wang, Haidong (Frontiers in Earth Science, 2025)
IntroductionThe Gangdese Tectonic Belt was formed through the prolonged subduction and collisional processes involving the Neo-Tethys Ocean and the Indian and Asian continental plates, preserving tectonic evolutionary imprints of both oceanic subduction and continental collision. However, the geodynamic mechanisms controlling Late Cretaceous magmatism in the Gangdese Tectonic Belt remain debated, necessitating further investigation into its magmatic evolution and geodynamic processes.MethodsThis study employs zircon U-Pb geochronology and geochemical analysis (including major, trace element, and Sr-Nd isotope data) on the Xietongmen granite and Longger granite from the Gangdese Tectonic Belt.ResultsThe Xietongmen granite formed at 96 Ma, while the Longger granite formed slightly later at 80 Ma. The Xietongmen granite can be classified as a high-K calc-alkaline and weakly peraluminous granite. Geochemically, it is enriched in Sr, depleted in Y, and exhibits high Sr/Y and (La/Yb)N ratios, displaying geochemical signatures comparable to adakite-like rocks. The Longger granite is a metaluminous granitoid of the high-K calc-alkaline series. Furthermore, the negative correlation of P2O5 with SiO2 and the presence of hornblende and biotite indicate that it belongs to the I-type granites. The Xietongmen and Longger granites were probably derived from the partial melting of the lower crust. The source of the Xietongmen granite may contain residual garnet and hornblende, while the Longger granite likely underwent plagioclase fractional crystallization. The initial (87Sr/86Sr)i ratios and εNd(t) values (2.78–3.76) of the Xietongmen granite may suggest derivation from a juvenile crustal source.DiscussionIntegrating the data of this study with previous research, the Xietongmen granite was likely formed due to Neo-Tethyan oceanic ridge subduction. In contrast, the Longger granite was formed during the slab rollback phase following ridge subduction.